Spiritual Tempat Kerja, Sikap Kerja Positif, dan Spiritualitas IndividualKaryawan (Studi pada PT. Pupuk Iskandar Muda (Persero) Lhokseumawe - Mahdani Mahdani (JURNAL EKOMBIS, 2018)
This study aimed to analyze the influence of workplace spirituality towards a positive work attitude and also analyze the effect of individual spirituality to the relationship between the workplace spirituality towards a positive work attitude.The study was conducted PT. Pupuk Iskandar Muda Lhokseumawe, the company’s employees as a unit of analysis. Samples were analyzed studies totaling 181 respondents.The method of data collection is the primary data collected through questionnaires distributed to respondents. Data analysis was performed using Multiple Regression (MR) and Moderated Regression Analysis (MRA),through the Statistical Package for Social Science (SPSS). The results showed there is effect of workplace spiritualitytoward a positive work attitude and individual spirituality contribute to both the relationship.Keyword: , individual spirituality, Positive work attitudes, Workplace spirituality.